Dampak Pembelajaran Berbasis Masalah dengan Dukungan Video Interaktif terhadap Kemampuan Berpikir Kritis Siswa SMP Negeri 3 Terara Lombok Timur 2025-2026 - Wahyudi Arsi; Syahrial Ayub; Galuh Permatasari (Mataram University, 2026)
This study aims to measure the impact of implementing the Problem Based Learning (PBL) model supported by interactive video on the critical thinking skills of students at SMP Negeri 3 Terara, East Lombok. The research employed a one-group pretest–posttest design with a sample of 36 seventh-grade students. The research instrument consisted of essay tests developed based on critical thinking indicators: analysis, evaluation, inference, explanation, and self-regulation. Data were analyzed using normalized N-gain to determine the level of improvement in students’ critical thinking skills. The findings revealed a significant increase across all indicators following the implementation of PBL assisted by interactive video. The analysis (0.72) and explanation (0.70) indicators were categorized as high, while evaluation (0.56), inference (0.63), and self-regulation (0.61) were categorized as moderate. These results confirm that integrating interactive video into PBL is effective in enhancing students’ critical thinking skills, particularly in the aspects of analysis and explanation, and provides practical contributions for science teachers in developing innovative learning strategies relevant to the demands of the 21st century.